2021
DOI: 10.1136/bmjgast-2021-000780
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for non-alcoholic fatty liver disease (NAFLD) and fibrosis among young adults in Egypt

Abstract: ObjectiveLimited literature has examined the epidemiology of non-alcoholic fatty liver disease (NAFLD) and fibrosis among young adults in Egypt, a country with one of the highest obesity rates globally. We assessed the prevalence of steatosis and fibrosis among college students in Egypt.DesignIn this cross-sectional study, we recruited students unaware of having fatty liver via a call-for-participation at a private university in the Dakahlia governorate of Egypt. Primary outcomes were the prevalence of steatos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…The prevalence of NAFLD among apparently healthy young Egyptian adults aged 19–21 year was studied by Tomah et al who concluded that fatty liver was present in 31.6% of them [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of NAFLD among apparently healthy young Egyptian adults aged 19–21 year was studied by Tomah et al who concluded that fatty liver was present in 31.6% of them [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, whole grain consumption can reduce the risk of dyslipidemia, CVD, and diabetes ( 37 , 80 , 104 ). Another feature of the MeD is low consumption of red and processed meat, including SFAs and cholesterol, which has been linked to NAFLD development in case-control and cross-sectional studies ( 11 , 105 ).…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is a multifactorial disease that involves many risk factors related to lifestyle and diet, including metabolic syndrome (MeS), obesity, type 2 diabetes mellitus, dyslipidemia, and insulin resistance (4,10). Indeed, several studies have demonstrated that obesity, diabetes, and MeS increase NAFLD risk (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…1,4,5 NAFLD is a benign condition; however, it may progress toward more serious diseases, including non-alcoholic steatohepatitis (NASH), fibrosis, cirrhosis, and ultimately, hepatocellular carcinoma (HCC) and cardiovascular disease mortality. 4,[7][8][9] The condition is thought to affect 25% of adults worldwide. 4,9,10 MicroRNAs (miRNAs) are small, noncoding RNAs comprising 18-25 nucleotides that alter gene expression by interfering at the post-transcriptional level.…”
Section: Introductionmentioning
confidence: 99%